(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Guduchyadi kwatham is a renowned Ayurvedic formulation used by Ayurvedic physicians all over India against influenza attacks and viral diseases. It is indicated for Pitta and Kapha aggravated conditions, Jwaram (Fever) and diseases of gastrointestinal system in classical Ayurvedic literature. Indications and pharmacological activities of the ingredients in respiratory diseases and Rakta (Blood) vitiated conditions suggest the use of this formulation in viral diseases that mainly involve respiratory system. In order to assess the pharmacological potential, Ayurvedic literature of the formulation and the pharmacological evaluations conducted with the part used and phytoconstituents of individual drugs were collected. Informations about the pathogenesis and symptomatology of COVID-19 were gathered from the recent research publications which were available online. Common symptoms of Coronavirus disease 2019 caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are fever, cough, sputum production, fatigue, headache, haemoptysis, diarrhoea, dyspnoea, and lymphopenia. When the disease progresses clinical conditions like Pneumonia, RNAaemia, acute respiratory distress syndrome, etc that lead to may develop death. Significantly increased level of leukocytes, pro-inflammatory cytokines and chemokines in plasma are seen during pathogenesis. The manifestation of systemic inflammatory response along with respiratory symptoms reveals that the main Doshas involved in this viral infection are Pitta and Kapha. The formulation possesses Pittakapha samana action and the ingredients are beneficial in diseases of Pranavahasrotas, Annavahasrotas, Rasavahasrotas and Raktavahasrotas. Pharmacological screening of drugs demonstrated anti-inflammatory, antipyretic, antiviral, antibacterial, anti allergic, antioxidant and immunomodulatory effects. Ayurvedic literature and findings of various phytochemical and pharmacological researches validate the use of Guduchyadi kwatham in the prevention and mitigation of this viral disease.